ELEKTRODEKOLORISASI LIMBAH CAIR ZAT WARNA BATIK DENGAN ELEKTRODA PbO2/Pb - Laksmi Dewi, Prihastuti Santini (Chem Info Journal, 2013)
Has done research on use of electrodecolorization batik dye wastewater using PbO2 and Pb electrodes. The purpose of this research are to decolorize batik dye wastewater by electrolysis using PbO2 and Pb batteries electrode, to decrease COD’s parameter and to increase quality of water after the treatment of dye waste batik’s by molecular filtration. This research was carried out by electrolyzing waste dye samples solution at potential of 9 volts using PbO2 as anode and Pb as cathode. Results were filtered by natural zeolite. Analysis including observing solution color, absorbance measurements by UV-Vis spectrophotometer and AAS’s instrument analysis, COD value of the sample before and after electrolysis, and after filtering. Results showed that electrolysis of dye waste batik using PbO2 anode was effective to decolorize that samples until 100% and to reduce COD value then molecular filtering of the sample could improve water quality by Fe reducing metal and Na+ ion on indigosol and remazol black B dye waste.